Pragmatics as an inspiration for language teaching - Hu, Yingli (Transactions on Economics, Business and Management Research, 2024)
This paper discusses the application value of pragmatics theory in language teaching practice. The article from the theory and practice of two levels of development. At the theoretical level, the basic principles of pragmatics, such as the cooperative principle and presupposition theory, have a profound impact on language understanding and production. At the practical level, the author advocates integrating pragmatic awareness into the classroom, improving students' pragmatic competence through case analysis, role playing and other interactive ways, so that they can flexibly use language in actual communication, instead of just mastering grammar rules and vocabulary knowledge. In addition, the paper also focuses on the role of cultural factors in pragmatic understanding, emphasizing that understanding and respecting cultural differences is the key to improving pragmatic competence in cross-cultural communication.